Memories of a black childhood in Maracanaú - Silva de Oliveira, Rebeca (2025)
The objective of this work is to understand, through autobiographical narrative, the aspects that make up the memory of the experience of a black childhood spent in Maracanaú, Ceará. Facing the city as a place of memory, the research intertwines the relationship between the history of the place and the private and community experiences that form local identity. Using a qualitative approach and autobiographical methodology, childhood memories are recovered, reflecting on the socio-economic and cultural context of Maracanaú. It is possible to perceive in these experiences the presence of Afro-descendant culture, through customs, food, festivities and traditions, as opposed to the constant devaluation of the memory and historical existence of this community in the municipality. Despite its problems, Maracanaú is the largest dormitory city and industrial hub in the state, which leads to difficulties in the sense of belonging and a lack of maintenance of historical and cultural heritage. The study aims to highlight the value of memory and self-narrative in preserving the history and identity of black and peripheral populations in an urban context.